(untitled) (GYMNASIUM, 2017)
The issue of emotional intelligence has become a reference point for research not only in the field of psychology. The field of team sports may constitute a very good environment for studying emotional intelligence. The study conducted in 2012 on the 11 components of the women’s volleyball team Ştiinţa Bacău of “Vasile Alecsandri” University, has made use of the Emotional Intelligence Test, adapted by Rocco after Bar-On and Goleman. The test aims both at transposing the individual into a certain situation as realistically as possible and also at providing the possibility to choose one out of the four possible answers. The data obtained has been processed and analyzed using the program Statistical Package for the Social Sciences. We intend to determine to what extent the results of the test may (re)confirm the collaborative strategy of the coaches and/or may suggest new game schemes involving the components of the team.